Transport phenomena of nanoparticles in plants and animals/humans - Anjum, Naser A.; Rodrigo, Miguel Angel Merlos; Moulick, Amitava; Heger, Zbynek; Kopel, Pavel; Zítka, Ondřej; Adam, Vojtech; Lukatkin, Alexander S.; Duarte, Armando C.; Pereira, Eduarda; Kizek, Rene (Environmental research, 2016)
The interaction of a plethora nanoparticles with major biota such as plants and animals/humans has been the subject of various multidisciplinary studies with special emphasis on toxicity aspects. However, reports are meager on the transport phenomena of nanoparticles in the plant-animal/human system. Since plants and animals/humans are closely linked via food chain, discussion is imperative on the main processes and mechanisms underlying the transport phenomena of nanoparticles in the plant-animal/human system, which is the main objective of this paper. Based on the literature appraised herein, it is recommended to perform an exhaustive exploration of so far least explored aspects such as reproducibility, predictability, and compliance risks of nanoparticles, and insights into underlying mechanisms in context with their transport phenomenon in the plant-animal/human system. The outcomes of the suggested studies can provide important clues for fetching significant benefits of rapidly expanding nanotechnology to the plant-animal/human health-improvements and protection as well. •Nanoparticles (NPs) are being indiscriminately used in multiple disciplines.•Plants and animals/humans are closely linked.•Plants and animals/humans can be exposed to indiscriminately used NPs.•Transport phenomena of NPs in plants and animals/humans are discussed.•Unveiling more insights into NPs-plant-animal/human interaction is required.